2019
DOI: 10.3390/ma12142228
|View full text |Cite
|
Sign up to set email alerts
|

Oxytree Pruned Biomass Torrefaction: Mathematical Models of the Influence of Temperature and Residence Time on Fuel Properties Improvement

Abstract: Biowaste generated in the process of Oxytree cultivation and logging represents a potential source of energy. Torrefaction (a.k.a. low-temperature pyrolysis) is one of the methods proposed for the valorization of woody biomass. Still, energy is required for the torrefaction process during which the raw biomass becomes torrefied biomass with fuel properties similar to those of lignite coal. In this work, models describing the influence of torrefaction temperature and residence time on the resulting fuel propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
4
17
0
Order By: Relevance
“…Therefore, there was an effect of concentrating the solid material, resulting in an increase of ash content in the fuel. Other biomass materials like wood sawdust and chips, investigated by Świechowski et al [53], also had a higher ash content at a higher temperature of the torrefaction process. Their research showed that torrefied pruned biomass (oxytree wood) at a temperature of 200 °C contained below 10% of ash.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there was an effect of concentrating the solid material, resulting in an increase of ash content in the fuel. Other biomass materials like wood sawdust and chips, investigated by Świechowski et al [53], also had a higher ash content at a higher temperature of the torrefaction process. Their research showed that torrefied pruned biomass (oxytree wood) at a temperature of 200 °C contained below 10% of ash.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results and using the best variant (T and t), a simple model [49] was proposed (after some modifications) for estimating the possibility of achieving heat self-sufficiency of biocoal production. The model also calculates the theoretical mass yield after biocoal recirculation of the torrefied biomass to maintain the torrefaction process itself (biocoal recirculation- Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Heat need for torrefaction process: Data for calculations [49]: The heat needed to heat water contained in MSC:…”
Section: Main Properties Of Torrefied Biomass Calculationsmentioning
confidence: 99%
“…where HHV-high heating value (on dry basis), MJ•kg -1 ; M f -fuel mass (on dry basis), mass, g; M ash -the mass of ash in fuel, g. Multiple regression analysis at the significance level p < 0.05 was then performed to elucidate the influence of process temperature and residence time on biochars fuel and fertilizer properties. Finally, the polynomial models of process temperature and residence time influence on biochars fuel properties were used according to the previous study [60] with regression modeling:…”
Section: Discussionmentioning
confidence: 99%